Co‐expression of alpha‐1 antitrypsin with cytoplasmic domain of v‐SNARE in Pichia pastoris: Preserving biological activity of alpha‐1 antitrypsin. (26th December 2017) - Khatami, Maryam; Hosseini, Seyed Nezamedin; Hasannia, Sadegh
Abstract: Alpha‐1‐antitrypsin (A1AT) is a major serum protein in human with protease inhibitory activity. Because of its extensive application in medicine, recombinant DNA technology has been considered for its production. The current study examines coexpression of A1AT and soluble domain of v‐SNARE in Pichia pastoris, which can prevent the secretion of A1AT after thoroughly passing the secretory pathway. This was done mainly to preserve the biological activity of A1AT, which in the secretory mode might be impaired in the fermentation and early clarification conditions. SNARE proteins are the driving force for vesicle docking and membrane fusion in the exocytosis. Intracellular expression of the cytoplasmic domain of v‐SNARE and its subsequent interaction to form SNARE complex can intensify the competition for A1AT secretory vesicles to be fused and released to the media. Our investigation shows successful coexpression of A1AT in the form of post‐Golgi vesicles and the cytoplasmic domain of v‐SNARE. Our findings confirmed the reduction of A1AT secretion by 45% caused accumulation of post‐Golgi secretory vesicles filled with A1AT inside the yeast cell. A1AT trapped in secretory vesicles were biologically more active than secretory A1AT. These results indicate that the inhibition of A1AT secretion can protect its biological activity in fermentation and clarification processes.